2022
DOI: 10.1155/2022/6706698
|View full text |Cite|
|
Sign up to set email alerts
|

Mental Health Evaluation Based on Visual Analysis Technology

Abstract: In order to solve the problems existing in the current mental health assessment system and how to better help individuals analyze their mental health, propose a mental health assessment method based on visual analysis technology; through the study of mental health assessment methods, use the SCL-90 symptom self-rating scale as the mental health assessment scale of this article. Combined with the conceptual design proposed in this article, realize a mental health assessment based on visual analysis technology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…e DV-Hop algorithm can solve various problems caused by low beacon point density [10]. Figure 1 shows the positioning process of the DV-Hop algorithm.…”
Section: Dv-hop Algorithmmentioning
confidence: 99%
“…e DV-Hop algorithm can solve various problems caused by low beacon point density [10]. Figure 1 shows the positioning process of the DV-Hop algorithm.…”
Section: Dv-hop Algorithmmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%